Adaptation of Gratitude Questionnaire-6 (GQ–6) in Indonesian Context - Dhanifa Veda Grimaldy; Handrix Chris Haryanto (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Adaptation of a psychological instrument is essential due to cultural difference and context. This study aimed to adapt the Gratitude Questionnaire-6 (GQ-6) in an Indonesian context. The initial steps included back-to-back translation, focus group discussion, expert judgements, and pilot study. From this procedure, five additional items were added to the original GC-6. The eleven final items were tested to 404 undergraduate students aged 18-24 years-old from several universities in Jakarta. The reliability test, the internal consistency, was examined by the Cronbach’s alpha coefficient, while the validity test, construct validity, was examined using exploratory factor analysis (EFA). The result of analysis showed good validity and reliability (Cronbach’s alpha: 0.789). This study concluded that 11-item gratitude questionnaire consistently measured gratitude in adolescents based on two factors: appreciation to the constant experience of life and appreciation towards individuals that take part in one’s life.